PRINCIPAL POLICY ANALYSIS OF ONLINE LEARNING SYSTEMS THE COVID-19 PANDEMIC - Astutik, Erwin (Idaarah: Jurnal Manajemen Pendidikan, 2022)
The current Covid-19 pandemic, which continues until 2021, has had a significant impact on the world of education, thus the majority of schools in Indonesia still use the online learning system. One of them is Sumput and Sarirogo villages. The implications of several policies that have been set by the government regarding the learning system during the pandemic require the leadership of school principals to support online learning. Based on these problems, this study was made to determine the principal’s policy on the online learning system during the pandemic. The research approach used is a descriptive quantitative method with the research instrument in the form of a questionnaire. While the data analysis used SPSS Version 16. Based on the results of the study, it was found that the form of policy that was mostly taken by school principals was the resource indicator with details, from 5 principals consisting of SDN Sumput, SDN Sarirogo, MI Nahdlatul Ulama Sarirogo, Darul Fikri Sarirogo Integrated Islamic Junior High School and Darul Fikri Sarirogo Integrated Islamic High School, 3 of which (SDN Sumput, Darul Fikri Sarirogo Integrated Islamic Junior High School and Darul Fikri Sarirogo Integrated Islamic High School) had the highest scores on the resource indicator. Meanwhile, the lowest form of policy is on social, economic and political indicators with details, out of 5 principals all have the lowest scores on social, economic and political indicators.